Delineating geological structure utilizing integration of remote sensing and gravity data: a study from Halmahera, North Molucca, Indonesia - Aprina, Patria Ufaira; Santoso, Djoko; Alawiyah, Susanti; Prasetyo, Nugroho; Ibrahim, Khalil (Vietnam Journal of Earth Sciences, 2024)
Halmahera Island is the result of the interaction between the Indo-Australian Plate, the Molucca Sea Plate, and the Philippine Plate, which gave rise to many active geological structures that are vulnerable to seismic activity around the island. The complexity of this geological structure makes Halmahera Island very interesting to study. This study aims to identify geological structures by integrating remote sensing and gravity satellite data. Surface lineament analysis using the remote sensing method was carried out based on Sentinel-1A imagery data. The gravity method uses GGMPlus satellite data to clarify the continuity of geological structures that cannot be clearly mapped on the surface. Lineament analysis on gravity data uses techniques such as fast sigmoid edge detection (FSED) and Euler deconvolution. The results of lineament interpretation based on integrating remote sensing and gravity satellite data show that the NE-SW structure controls the northern and northeastern arms of Halmahera. In contrast, the southern arm is dominated by the NW-SE structure. The Euler depth estimation shows that the Halmahera area contributes to having geological structures at various depths. Deep structures reach 4 km, while shallow structures are found at depths of up to 2 km. Earthquake hypocenter data strengthen the interpretation of this geological structure. This comprehensive study yields an excellent correlation between gravity and remote sensing techniques in describing the general structural framework of the area. The new finding is an NE-SW trending geological structure on the northern Halmahera arm, which may be caused by two different tectonics first, the subduction of the Molucca Sea Plate with the Halmahera Plate in the west. Second, the strike-slip movement is trending NE-SW, which cuts the northern and northeastern arms due to the rotational movement of the thrust fault with the Philippine Plate to the west.